1990
DOI: 10.1113/jphysiol.1990.sp018104
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the corticospinal tract by electromagnetic and electrical stimulation of the scalp in the macaque monkey.

Abstract: SUMMARY1. The responses evoked by non-invasive electromagnetic and surface anodal electrical stimulation of the scalp (scalp stimulation) have been studied in the monkey. Conventional recording and stimulating electrodes, placed in the corticospinal pathway in the hand area of the left motor cortex, left medullary pyramid and the right spinal dorsolateral funiculus (DLF), allowed comparison of the actions of non-invasive stimuli and conventional electrical stimulation.2. Responses to electromagnetic stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
149
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(168 citation statements)
references
References 23 publications
(29 reference statements)
17
149
1
Order By: Relevance
“…TMS produces multiple descending volleys over several milliseconds with some corticospinal neurons firing more than once (Edgley et al, 1990;Rothwell et al, 1991). Our timing was based on estimates of the arrival of the first descending volley at the motoneuron, but clearly timing of later volleys is also likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…TMS produces multiple descending volleys over several milliseconds with some corticospinal neurons firing more than once (Edgley et al, 1990;Rothwell et al, 1991). Our timing was based on estimates of the arrival of the first descending volley at the motoneuron, but clearly timing of later volleys is also likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial magnetic stimulation of the human brain causes short latency facilitation of the motoneurones of forearm and hand muscles which has been attributed to the excitation of fast corticospinal neurones (Hess, Mills & Murray, 1987;Day, Dressler, Maertens de Noordhout, Marsden, Nakashima, Rothwell & Thompson, 1989), at the initial segment (Edgley et al 1990). Fast conducting MOTOR CORTEX STIMULATION AND MUSCLE STRETCH corticospinal neurones make monosynaptic connections with motoneurones of hand and forearm muscles in primates, based on physiological (Bernhard & Bohm, 1954;Phillips & Porter, 1964) and histological (Lawrence, Porter & Redman, 1985) evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This was considered to be compatible with summation occurring at the cortex, although, since there was no measure of the size of the descending volleys and since rectified electromyography does not permit precise timing of events, it was not possible to exclude the excitation of different subsets of motoneurones, non-linear responses of a population of motoneurones to descending volleys, or summation occurring at interneurones (Day et al 1991). This differential facilitation was observed with magnetic stimulation (believed to excite cortical neurones) but not with electrical stimulation over the cortex (thought to excite the axons of cortical cells (Edgley, Eyre, Lemon & Miller, 1990)). This implies that there were changes in the excitability of cortical neurones unless the two forms of stimulation excited different populations of cortical neurones with different effects on spinal neurones.…”
Section: Introductionmentioning
confidence: 99%
“…Since the CM system can be activated by magnetic brain stimulation (Edgley, Eyre, Miller & Lemon, 1990: see Rothwell, Thompson, Day, Boyd & Marsden, 1991), it is interesting to investigate whether the muscle responses this evokes behave in a task-related fashion. Datta, Harrison & Stephens (1989) found that EMG responses in the first dorsal interosseous muscle (1DI) were larger in an 'isolated' isometric abduction of the index finger than when the same muscle was used in concert with other muscles during a power grip.…”
Section: Introductionmentioning
confidence: 99%